Systematic modifications of BTP-type ligands and effects on the separation of trivalent lanthanides and actinides - Beele, Björn B.; Schwörer, Felicitas; Panak, Petra (Procedia chemistry, 2012)
In this study the separation of Am(III) from Eu(III) in nitric acid using two BTP-type N-donor ligands, 2,6-bis(6-ethyl-1,2-diazine-3-yl)pyridine (Et-BDP) and 2,6-bis(4-npropyl-2,3,5,6-tetrazine-1-yl)pyridine (nPr-tetrazine) is presented. The extraction and separation properties of both ligands are tested by two phase liquid-liquid extraction at different acid concentrations. In contrast to nPr-BTP the bisdiazinyl ligand Et-BDP is prone to protonation at nitric acid concentrations of 0.2M and higher. A separation factor of SFAm/Eu ≈ 5 is obtained using Et-BDP as extracting ligand and with nPr-tetrazine a SFAm/Eu of 9.1 is realized. Hereby 2-bromodecanoic acid as lipophilic anion source is needed.
Gesehen am 02.11.2018